Quality of Life in Pediatric Mild Traumatic Brain Injury and its Relationship to Postconcussive Symptoms - Moran, Lisa M. (Oxford University Press, 2012)
Objectives Mild traumatic brain injury (TBI) and injury-related outcomes such as postconcussive symptoms (PCS) may influence health-related quality of life (HRQOL) in children. Methods We evaluated HRQOL in 186 8- to 15-year-old children with mild TBI and 99 children with orthopedic injuries (OI). Parents rated the frequency and severity of PCS at an initial assessment within 2-weeks postinjury and rated HRQOL at 3- and 12-months postinjury. Results The mild TBI and OI groups did not differ in psychosocial HRQOL, but the mild TBI group showed lower physical HRQOL at the 12-month follow-up. Somatic PCS were a significant predictor of physical HRQOL over time, and both cognitive and somatic PCS were significant predictors of psychosocial HRQOL over time. Children with higher PCS at the initial assessment had lower HRQOL scores at later time points. Conclusions Effective management of PCS may be associated with improvements in HRQOL following pediatric mild TBI.